Are banks going with the flows? An empirical assessment of the international credit channel in the Pacific Alliance countries (2021)
Based on a cross-country bank-level analysis within four emerging market countries in Latin America from 2016 to 2019, this document addresses how international capital flows impact banks' loan supply and risk, and if these effects are contingent upon the banks' funding strategies. Our identification strategy relies on the VIX index as a measure of the global financial cycle to instrument debt capital inflows in a two-stage least squares framework. Our main findings are that as debt portfolio inflows increase 10%, the net loan portfolio expands 0.7% and the insolvency risk exposure increases 1.0%, ceteris paribus. Testing whether these results are subject to the type of funding, we stress out that a higher concentration of non-core funds in the liabilities side of the balance sheet amplifies -rather than mitigates- the former results. As extensions to our baseline model, we provide evidence that capital inflows impact is differential across types of non-core funding (bonds vs. credits) and bank's ownership (foreign-owned vs. domestic).